2023
DOI: 10.1093/ckj/sfad039
|View full text |Cite
|
Sign up to set email alerts
|

New and old GFR equations: a European perspective

Abstract: Glomerular filtration rate (GFR) is estimated in clinical practice from equations based on the serum concentration of endogenous biomarkers and demographic data. The 2009 creatinine-based CKD-EPI equation (CKD-EPI2009) was worldwide recommended until 2021, when it was recalibrated to remove the African-American race factor. The CKD-EPI2009 and CKD-EPIcr2021 equations overestimates GFR of adults aged 18 to 30 years, with a strong overestimation in eGFR at age 18. CKD-EPICr2021 does not perform better than CKD-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…As expected, the prevalence of chronic kidney disease was greater in the RH + MAU group, as classi ed according to the creatinine-based Chronic Kidney Disease Epidemiology Collaboration equation (CKD-EPI 2009 ) (52). In this case, an estimated glomerular ltration rate (eGFR) < 60 mL/min/1.73 m 2 is considered to represent mild renal insu ciency for both men and women.…”
Section: Discussionmentioning
confidence: 66%
“…As expected, the prevalence of chronic kidney disease was greater in the RH + MAU group, as classi ed according to the creatinine-based Chronic Kidney Disease Epidemiology Collaboration equation (CKD-EPI 2009 ) (52). In this case, an estimated glomerular ltration rate (eGFR) < 60 mL/min/1.73 m 2 is considered to represent mild renal insu ciency for both men and women.…”
Section: Discussionmentioning
confidence: 66%
“…The CKD Epidemiology Collaboration (CKD-EPI) equation was developed in an effort to create a more precise formula for eGFR, especially if the actual GFR is more than 60 mL/min per 1.73 m 2 [ 26 , 27 ]. Since the aMDRD formula for calculating GFR currently used in Taiwan is based on a Western population, this study suggests that in subsequent studies to validate the formula for assessing renal function, risk factors that are more suitable for the Taiwanese population should be added to establish a local formula that is more compatible with this population.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, testing the efficacy of nephroprotection at an early stage of CKD is the main aim of clinical research. The role of eGFR for clinical and research purposes has been already developed in several review articles as reported in Table 1 [ 9 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], whereas the main contents and novelties of the present review are repored in Table 2 (Ref. [ 6 , 60 , 62 , 63 , 64 , 68 ]).…”
Section: Egfr As Endpoint Biomarkermentioning
confidence: 99%